THE ROLE OF STATIN THERAPY IN ADIPOSE TISSUE. (April 2021) - Sanidas, Elias; Papadopoulos, Dimitrios; Velliou, Maria; Zerva, Kanella; Tsakalis, Konstantinos; Fotsali, Anastasia; Iliopoulos, Dimitrios; Mantzourani, Marina; Toutouzas, Konstantinos; Barbetseas, John
Abstract : Objective: The hormones of adipose tissue, so called adipokines, possess either anti-inflammatory (apelin) or pro-inflammatory (chemerin) properties affecting local and systemic inflammation. Nonetheless, statins have potent anti-inflammatory effects in tissues and organs contributing to favorable outcomes. The aim of this study was to calculate apelin and chemerin adipokines plasma levels in patients with impaired lipid levels receiving statins exploring another potential pleotropic impact of statin therapy. Figure. No caption available. Design and method: Overall, 127 patients were studied. Of them, 66 were treated with statins and 61 were not. Apelin and chemerin plasma levels were measured by the Elisa method. Results: Apelin levels were higher in patients treated with statins while chemerin levels were lower. No significant differences in demographic characteristics, arterial hypertension and diabetes mellitus were observed between the two groups (Table). Conclusions: The anti-inflammatory adipokine apelin was increased in patients receiving statins whereas the pro-inflammatory adipokine chemerin was decreased underlining an alternative anti-inflammatory effect of statin therapy.